2015
DOI: 10.1371/journal.pone.0124519
|View full text |Cite
|
Sign up to set email alerts
|

Traces of Unconscious Mental Processes in Introspective Reports and Physiological Responses

Abstract: Unconscious mental processes have recently started gaining attention in a number of scientific disciplines. One of the theoretical frameworks for describing unconscious processes was introduced by Jung as a part of his model of the psyche. This framework uses the concept of archetypes that represent prototypical experiences associated with objects, people, and situations. Although the validity of Jungian model remains an open question, this framework is convenient from the practical point of view. Moreover, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…23 Pranayama is the fourth limb and meditation is the seventh limb of ashtanga yoga. The real meaning of pranayama is control of bio-energy.…”
Section: Pranayama In Medical Educationmentioning
confidence: 99%
“…23 Pranayama is the fourth limb and meditation is the seventh limb of ashtanga yoga. The real meaning of pranayama is control of bio-energy.…”
Section: Pranayama In Medical Educationmentioning
confidence: 99%
“…Since the structure of stories is suggested to be universal to a certain level, research into the emotional experiences built upon this storyline is thus a promising direction to proceed. This typical kind of experience was called "archetypal experience," and evidence has suggested that it introduces unique physiological patterns that can be recognized with significance (Ivonin et al 2015). While the preliminary findings are promising, various genres of movies are yet to be studied.…”
Section: Mapping Media Experience With the Storylinementioning
confidence: 99%
“…Regarding the unconscious emotions in media content, some preliminary studies have revealed that specific narratives in media content would induce unique physiological patterns while the audience is unaware of it (Ivonin et al , 2014(Ivonin et al , 2015Chang et al 2014b). It is promising to explore further with this direction.…”
Section: Potential Challenges and Promising Approachesmentioning
confidence: 99%
“…al [4] found that the amount of heuristics should not be too vast as redundancy then might occur and that they should be presented similarly to Nielsen's usability heuristics [4]. Psycho-physiological measures in games: The domain of psycho-physiological research has been described as being concerned with trying to decipher mental processes, by measuring the body's signals and thereby finding links between them [6]. Emotions are a core element in experience and using psycho-physiological measures to recognizing a user's emotional state, is utilized across fields that share related psycho-physiological states, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Emotions are a core element in experience and using psycho-physiological measures to recognizing a user's emotional state, is utilized across fields that share related psycho-physiological states, e.g. arousal [6]. While a full breakdown of all relevant related work on psycho-physiological measures in GUR is out of scope here, a mention is made of work that utilizes the same measures in surrounding fields.…”
Section: Introductionmentioning
confidence: 99%